Evaluation on the Control Effects of Different Biogenic Pesticides Mixed with Metarhizium anisopliae CQMa421 on Empoasca onukii Matsuda - Jingjing LI; Kui KANG; Wenxuan QI; Jinghui SUN; Zhangli FENG; Daowei ZHANG (Guangdong nongye kexue)
【Objective】The field control effects of different biogenic pesticides on Empoasca onukii Matsuda (tea green leafhopper) was investigated, with an aim to provide a basis for the rational application of pesticides in tea gardens.【Method】Using a five-point sampling method, based on the investigation of the dynamic occurrence of E. onukii with yellow sticky traps in Zunyi of Guizhou Province, the field control effects of seven different biological pesticides biogenic pesticides spinetoram, azadirachtin and veratrine and their mixture with Metarhizium anisopliae CQMa421 (500-fold dilution) were evaluated, water was used as the control (CK).【Result】The results showed that E. onukii occurred in seven generations in Zunyi area from March to September 2021 (during tea picking period), with severe alternation between generations. And the number of E. onukii reached its peak of 899 in late June. The rise in temperature facilitated the initial reproduction of E. onukii, with the population gradually increasing with the temperature until it reached the peak period. The highest control effect single use of Metarhizium anisopliae CQMa421 against E. onukii was 63.22%, which was achieved 7 d after application. The highest control effects of single use of spinetoram, azadirachtin and veratridine against E. onukii was achieved 3 d after application and were 90.14%, 62.82% and 61.04%, respectively. The control effect of spinetoram, azadirachtin and veratridine mixed with M. anisopliae CQMa421 was higher than that of using CQMa421 only, with control effects at 3 d post-application being 87.12%, 71.41% and 72.86%, respectively. It was established the economic costs required for applying different combinations of pesticides in a 333 m2 tested tea garden, from lowest to highest, were as follows: spinetoram (20 yuan), veratrine (22 yuan), azadirachtin (24 yuan), spinetoram + CQMa421 (35 yuan), veratrine + CQMa421 (36 yuan), azadirachtin + CQMa421 (37 yuan), and CQMa421 (50 yuan).【Conclusion】The effects of single use of bio-pesticides against E. onukii ranked as: spinetoram > M. anisopliae CQMa421 > azadirachtin > veratrine; the effects of the combined use of bio-pesticides with M. anisopliae CQMa421 against E. onukii ranked as: spinetoram > veratrine > azadirachtin. In the actual application of pesticide in tea garden, spinetoram is recommended because of its fast, good and long-lasting control effect as well as low economic cost, and it is an excellent synergist of M. anisopliae CQMa421 to control E. onukii.